Comprehensive Analysis Reveals the Genetic and Pathogenic Diversity of Ralstonia solanacearum Species Complex and Benefits Its Taxonomic Classification - Geng, Ruimei; Cheng, Lirui; Cao, Changdai; Liu, Zhengwen; Liu, Dan; Xiao, Zhiliang; Wu, Xiuming; Huang, Zhenrui; Feng, Quanfu; Luo, Chenggang; Chen, Zhiqiang; Zhang, Zhenchen; et al. (Frontiers in Microbiology, 2022)
Ralstonia solanacearum species complex (RSSC) is a diverse group of plant pathogens that attacks a wide range of hosts, causing devastating losses globally. In this study, we conducted a comprehensive analysis of 121 RSSC strains to detect their genetic diversity, pathogenicity and evolutionary dynamics. Average nucleotide identity analysis was performed to explore the genomic relatedness among these strains, and finally obtained an open pangenome with 30,763 gene families. To better understand the diverse evolutionary and pathogenicity, we also conducted a series of analyses of virulence factors (VFs) and horizontal gene transfer (HGT) in the pangenome and at the single genome level. The distribution of VFs and mobile genetic elements (MGEs) showed significant differences among different groups and strains, which were consistent with the new nomenclatures of the RSSC with three distinct species. Further functional analysis showed that most HGT events conferred from Burkholderiales and played a great role in shaping the genomic plasticity and genetic diversity of RSSC genomes. Our work provides insights into the genetic polymorphism, evolutionary dynamics, and pathogenetic variety of RSSC, and provides strong supports for the new taxonomic classification, as well as abundant resources for studying host specificity and pathogen emergence.